The Correlation Between Demographic Factors (Education, Occupation, and Risk Zonation of Covid – 19) and Anxiety Levels of Pregnant Women During The Covid – 19’s Pandemic - Ida Fauziah; Putri Dwi Christanti; Tri Krianto (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: The Covid-19 pandemic had an impact on several sectors including the health sector, especially maternal and child health services. The policies and restrictions imposed during the Covid-19 pandemic certainly caused MCH services did not function optimally, even pregnant women's visits to health services were recorded to decline during the start of the pandemic before the introduction of new normal. This condition certainly has a substantial negative psychological effect, especially for pregnant women. Purpose: to determine the correlation between demographic factors and anxiety levels of pregnant women during the pandemic. Methods: This research used quantitative research by using an online questionnaire with a cross-sectional study design, and the number of respondents was 122 people using purposive sampling technique. Results: As many as 66% of respondents with higher education level, with the type of activity 58% work, as many as 45% live in the red zone or high risk of covid-19, and 72% were inhighlevel of anxiety. The results of statistical tests between the level of education, occupation, and risk zonation of covid – 19 on the level of anxiety, respectively, with p-values ??of 0.079, 0.256, and 0.546 Conclusion: Statistically, there was no correlation between the level of education, occupation, and risk zonation for Covid-19 on the level of anxiety of pregnant women in carrying out antenatal care.Health care providers are advised to provide extra services to pregnant women during the new normal era by providing service options through teleconsultation and tele-registration to shorten the duration of interaction and reduce the risk of exposure to the COVID-19 virus.